Estágio supervisionado em enfermagem: visão de preceptores - Oliveira, Aline Galúcio de (2014)
The present study aimed to analyze the vision of tutors from a university hospital about supervised internship in nursing. It is a descriptive nature research with qualitative approach, developed at the University Hospital Onofre Lopes (HUOL), located in Natal/RN. The population was composed of eleven assisting nurses engaged the precentorship of undergraduate course students in nursing, from the Federal University of Rio Grande do Norte (UFRN). For the empirical research, conducted in the period from September to November 2013, the semi-structured interview involving questions directed to the stage was used, as advocate the national curriculum guidelines, as regards this curricular component. With the consent of the institution where the study has been developed and approved by the Research Ethics Committee of UFRN, as n° 17800613.9.0000.5537, besides CAAE signing an informed consent by participants. The analysis of the information was held from the analysis of content, thematic mode. Thereby four categories were defined a priori, namely: the supervised internship in the vision of nurses; To be preceptor; The internship concerned: contributions and difficulties; Do the institutional actors communicate? The results indicate that in the view of the supervised internship preceptors is a sine qua non for the training of nurses, considering that it prepares for professional life. Besides being a moment conducive to the exercise of management and a greater rapprochement between theory and practice, stimulates the preceptor to upgrade to better exercise the function and also provides an exchange of knowledge between students and tutors, thus contributing to optimize the service. Nevertheless, the respondents indicate the existence of a distancing and little communication with the academic institution. In summary, it is realized that the nurses understand the importance of its function of tutors and supervised stage for vocational training. It is necessary, however, to reflect on the paths to be pinched in the confrontation of difficulties in this process, especially as regards the teaching/service relationship, which, while remaining at a distance, strengthens the existing dichotomy between theory and practice